Physiological and Proteomic Analysis of Different Molecular Mechanisms of Sugar Beet Response to Acidic and Alkaline pH Environment - Geng, Gui; Wang, Gang; Stevanato, Piergiorgio; Lv, Chunhua; Wang, Qiuhong; Yu, Lihua; Wang, Yuguang (Frontiers in Plant Science, 2021)
Soil pH is a major constraint to crop plant growth and production. Limited data are available on sugar beet growth status under different pH conditions. In this study, we analyzed the growth status and phenotype of sugar beet under pH 5, pH 7.5, and pH 9.5. It was found that the growth of sugar beet was best at pH 9.5 and worst at pH 5. The activities of superoxide dismutase (SOD) and peroxidase (POD) in leaves and roots increased as pH decreased from 9.5 to 5. Moreover, compared with pH 9.5, the levels of soluble sugar and proline in leaves increased significantly at pH 5. To explore the mechanisms of sugar beet response to different soil pH environments, we hypothesized that proteins play an important role in plant response to acidic and alkaline pH environment. Thus, the proteome changes in sugar beet modulated by pH treatment were accessed by TMT-based quantitative proteomic analysis. A total of three groups of differentially expressed proteins (DEPs) (pH 5 vs. pH 7.5, pH 9.5 vs. pH7.5 and pH 5 vs. pH 9.5) were identified in the leaves and roots of sugar beet. Several key proteins related to the difference of sugar beet response to acid (pH 5) and alkaline (pH 9.5) and involved in response to acid stress were detected and discussed. Moreover, based on proteomics results, QRT-PCR analysis confirmed that expression levels of three N transporters (NTR1, NRT2.1, and NRT2.5) in roots were relatively high under alkaline conditions (pH 9.5) compared with pH 5 or pH 7.5. The total nitrogen content of pH 9.5 in sugar beet was significantly higher than that of pH 7.5 and pH 5. These studies increase our understanding of the molecular mechanism of sugar beet response to different pH environments.